Up-regulation of proliferative and migratory genes in regulatory T cells from patients with metastatic castration-resistant prostate cancer - Huen, Ngar-Yee (2013)
A higher frequency of regulatory T cells (Tregs) has been observed in peripheral blood mononuclear cells (PBMC) of patients with different types of solid tumors and hematological malignancies as compared to healthy donors. In prostate cancer patients, Tregs in PBMC have been shown to have increased suppressive function. Tumor-induced biological changes in Tregs may enable tumor cells to escape immunosurveillance. We performed genome-wide expression analyses comparing the expression levels of more than 38,500 genes in Tregs with similar suppressive activity, isolated from the peripheral blood of healthy donors and patients with metastatic castration-resistant prostate cancer (mCRPC). The differentially expressed genes in mCRPC Tregs are involved in cell cycle processes, cellular growth and proliferation, immune responses, hematological system development and function, and the IL-2 and TGF-β pathways. Studies revealed that the levels of expression of genes responsible for T-cell proliferation (C-FOS, C-JUN, and DUSP1) and cellular migration (RGS1) were greater in Tregs from mCRPC patients as compared to values observed in healthy donors. Increased RGS1 expression in Tregs from mCRPC patients suggests a decrease in these Tregs’ migratory ability. Additionally, the higher frequency of CD4(+)CD25(high)CD127(−) Tregs in the peripheral blood of mCRPC patients may be the result of an increase in Treg proliferation capacity. Results also suggest that the alterations observed in gene expression profiles of Tregs in mCRPC patients may be part of the mechanism of tumor escape from host immune surveillance.